Perkembangan Kebijakan Pesantren, Madrasah, dan Sekolah Islam Terpadu di Indonesia - DR MURSAL, DR MURSAL (LPPM Institut Agama Islam Diniyyah Pekanbaru, 2024)
Abstrack In Indonesian history, there are 3 Islamic educational institutions that are interesting to study, namely Islamic boarding schools and integrated Islamic schools. The emergence of these 3 institutions was motivated by government policy conditions and political, economic, social conditions and the needs of the community itself. The research question that this research wants to answer is what are the dynamics of Islamic education institutions, Islamic boarding schools, madarsahs and integrated Islamic schools. Meanwhile, the research methods used in this research are descriptive, analytical and argumentative methods. Where the author looks for sources in the form of journals, books, articles related to the dynamics of Islamic educational institutions, Islamic boarding schools, madrasas. The results of the research in this study are that Islamic boarding schools and integrated Islamic schools are Islamic educational institutions that grow and develop in accordance with the needs and desires of the community itself, although these 3 institutions have their own characteristics and characteristics. Islamic boarding schools prioritize religion, madrasas 70 general 30 religions, while integrated Islamic schools prioritize aspects of Tahfizh, language and moral cultivation. Keywords: Islamic boarding school, Madrasah, Integrated Islamic School. Abstrak Dalam Sejarah Indonesiaada 3 lembaga pendidikan Islam yang menarik untuk dikaji yaitu pesantren madrsah dan sekolah Islam terpadu. Munculnya ke 3 lembaga tersebut dilatar belakangi oleh kondisi kebijakan pemerintah dan kondisi politik, ekonomi, sosial beserta kebutuhan dari masyarak itu sendiri. Pertanyaan penelitian yang ingin dijawanb dalam penelitian ini adalah bagaimana dinamika kelembagaan Pendidikan Islam, pesantren, madarsah dan sekolah Islam terpadu. Sedangkan metode penelitian yang dibuat dalam penelitian ini adalah dengan metode deskriftif, analitik dan argumentatif. Dimana penulis mencari sumber –sumber berupa jurnal, buku, artikel yang berkaitan dengan dinamika perkembangan lembaga pesantren, madrasah. Hasil penelitian dalam kajian ini adalah bahwa pesantren madrsah dan sekolah Islam terpadu merupakan lembaga pendidikan Islam tumbuh dan berkembangan sesuai dengan kebutuhan dan keinginan masyarakat itu sendiri, walaupun 3 lembaga ini mempunyai ciri dan khas masing masing. Pesantren mengedepankan agama, madrasah 70 umum 30 agama Sedangkan sekolah Islam terpadau mengedepankan aspek Tahfizh, bahasa dan penaman ahlak. Kata Kunci : Pesantren, Madrasah, Sekolah Islam Terpadu.